Effect of Red Betel Leaf (Piper crocatum) on Leucorrhea - Argaheni, Niken Bayu; Suryaningsih, Anis; Hutomo, Cahyaning Setyo (Jurnal Kebidanan, 2024)
Women have many problems in the area vagina. Most cases that occur are vaginal discharge. Leucorrhoea or in medical language called flour albus is the exit excessive fluid from the vagina. This study to determine the effect of red betel on vaginal discharge. Systematic review using the database: Google Scholar. The search results that meet the criteria are then analyzed for articles.  The result shows that water red betel leaf stew can overcome vaginal discharge experienced by women.